Massive stars reveal variations of the stellar initial mass function in the Milky Way stellar clusters - Dib, Sami; Schmeja, Stefan; Hony, Sacha (Monthly notices of the Royal Astronomical Society, 2017)
We investigate whether the stellar initial mass function (IMF) is universal, or whether it varies significantly among young stellar clusters in the Milky Way. We propose a method to uncover the range of variation of the parameters that describe the shape of the IMF for the population of young Galactic clusters.These parameters are the slopes in the low and high stellar mass regimes, γ and Γ, respectively, and the characteristic mass, Mch. The method relies exclusively on the high-mass content of the clusters, but is able to yield information on the distributions of parameters that describe the IMF over the entire stellar mass range. This is achieved by comparing the fractions of single and lonely massive O stars in a recent catalogue of the Milky Way clusters with a library of simulated clusters built with various distribution functions of the IMF parameters. The synthetic clusters are corrected for the effects of the binary population, stellar evolution, sample incompleteness, and ejected O stars. Our findings indicate that broad distributions of the IMF parameters are required in order to reproduce the fractions of single and lonely O stars in Galactic clusters. They also do not lend support to the existence of a cluster mass-maximum stellar mass relation. We propose a probabilistic formulation of the IMF whereby the parameters of the IMF are described by Gaussian distribution functions centred around γ = 0.91, Γ = 1.37, and Mch = 0.41 M⊙, and with dispersions of σγ = 0.25, σΓ = 0.60, and $ $σ _{M_{{\rm ch}}}=0.27$ $ M⊙ around these values.
Published: 28 September 2016
Gesehen am 27.10.2017